Functional Abilities of Stroke Survivors who Received Services at Community Rehabilitation Center - Chinchai, Pisak; Jindakham, Nathee; Apichai, Sopida (Journal of Associated Medical Sciences, 2017)
Background: Numbers of people with disabilities resulting from stroke are increasing in Thailand. Major sequela following a disease is weakness in one side of body which causes difficulty in functional abilities to those survivors. Community-based rehabilitation can be one of the potential strategies that enhance functional performance in individuals with disabilities. Objectives: Purpose of the present study was to investigate functional abilities of stroke survivors who received services provided by trained village health volunteers (VHVs) for a period of 3 months at their own community rehabilitation center. Materials and methods: This study was a one group pretest-posttest research design. Twenty-five stroke subjects were recruited by purposive sampling from 4 community rehabilitation centers in Chiang Mai Province and compared their functional abilities at before and after receiving the treatment program. Instrument used was Test of Activities of Daily Living (ADL) Performance. Statistics used were descriptive and paired t-test. Results: Results demonstrated that total score of functional abilities in stroke participants was higher at post intervention ( X =90.60±13.36) than at pretest ( X =85.24±18.88) significantly (p<0.05). In addition, comparisions of components of functional abilities in these individuals revealed that average scores at posttest of self-care abilities ( X =33.40±5.10) and social skills ( X =4.16±1.80) were significantly greater than those at pre-test where X =30.60±8.55 and X =3.08±1.61 respectively (p<0.05). Conclusion: It was indicated that community rehabilitation centers operated by trained VHVs could promote functional abilities especially in areas of self-care and social skills of people with disabilities who come for their services.